Differences in perception and use of residential spaces in selected multigenerational households - Oabel, Rucci Anne; Quevedo, Ma. Teresa P. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT The study is a qualitative research that examined the differences in perceptions and the use of residential spaces of each generation in order to determine their impact on the individual and collective lifestyle in a multigenerational household. A multi-method approach was employed in data gathering including survey, face to face interview, and photo documentation. This study was conducted on six (6) middle-income multigenerational households in Laguna. A total of eighteen (18) participants, with six (6) persons from each category: older, middle, and younger generations, were selected using purposive sampling. For the data collection, a survey questionnaire, an interview guide, a camera, and a voice recorder were used. The findings of the study suggested that the traditional use of the residential spaces were retained but emerging purposes arose as a result of each generation's distinct needs. The significance of each space to each generation was based on the types of activities and functions it supported. The results showed that issues and concerns were prevalent in the use of space of the older and younger generations. Values were manifested by each generation in their perceptions and use of space particularly in avoiding conflicts. Moreover, the key findings revealed that the differences in the use of space had more impact on the individual and collective lifestyles of the members than the differences in perception of spaces for it often influenced their behavior as well as their activities. Overall, individual lifestyles of the older generations were prioritized while the individual lifestyles of the younger generations were restrained. It also had a positive impact on the collective lifestyles of the members since they valued harmony and also because it centered on the principles of seniority, respect, and pakikisama.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Space (Architecture); Interior architecture